2022
DOI: 10.1097/iae.0000000000003363
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Half-Dose Photodynamic Therapy Versus High-Density Subthreshold Micropulse Laser for Treating Pigment Epithelial Detachments in Chronic Central Serous Chorioretinopathy

Abstract: Half-dose photodynamic therapy leads to a significantly larger decrease in the height of the highest macular pigment epithelial detachment compared with high-density subthreshold micropulse laser treatment in chronic central serous chorioretinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These areas of hyperfluorescence correspond to choroidal vascular hyperpermeability and illustrate the ability of PDT to remodel the choroid and presumably alleviate the hydrostatic pressure from the choroid towards the retina. Indeed, this exact consequence of half-dose PDT was investigated by Feenstra et al (2022), who found that half-dose PDT was superior to SML in terms of reduction in RPE detachments in cCSC. The reduction in macular RPE detachments may reflect that the hydrostatic pressure from the choroid towards the retina is markedly reduced, facilitating SRF resolution through a reconstitution of a more normal equilibrium of the micro-environment of the neuroretina, RPE and choroid.…”
Section: Discussionmentioning
confidence: 99%
“…These areas of hyperfluorescence correspond to choroidal vascular hyperpermeability and illustrate the ability of PDT to remodel the choroid and presumably alleviate the hydrostatic pressure from the choroid towards the retina. Indeed, this exact consequence of half-dose PDT was investigated by Feenstra et al (2022), who found that half-dose PDT was superior to SML in terms of reduction in RPE detachments in cCSC. The reduction in macular RPE detachments may reflect that the hydrostatic pressure from the choroid towards the retina is markedly reduced, facilitating SRF resolution through a reconstitution of a more normal equilibrium of the micro-environment of the neuroretina, RPE and choroid.…”
Section: Discussionmentioning
confidence: 99%
“…With 179 patients enrolled, improvement in BCVA and rate of SRF resolution was significantly greater in the half-dose PDT group compared with the SMPL group 40 . Subsequent analyses showed similar superiority of PDT over SMPL in secondary metrics such as improvement in PEDs and resolution of ICGA abnormalities 41,42 . These results were further underscored by the subsequent REPLACE trial, in which patients from the PLACE trial with persistent SRF received crossover treatment.…”
Section: Non-pdt Laser Therapymentioning
confidence: 92%
“…40 Subsequent analyses showed similar superiority of PDT over SMPL in secondary metrics such as improvement in PEDs and resolution of ICGA abnormalities. 41,42 These results were further underscored by the subsequent REPLACE trial, in which patients from the PLACE trial with persistent SRF received crossover treatment. Crossover from SMPL to PDT yielded improvements in visual and anatomic measures that were not seen with PDT to SMPL crossover.…”
Section: Non-pdt Laser Therapymentioning
confidence: 97%
“…2,[12][13][14] During PDT, the photosensitizer verteporfin is applied intravenously and then activated after 15 minutes by a 689-nm laser in a predefined area of the retina. In many patients, this results in a remodeling of the choroid, decreasing abnormal choroidal thickness and hyperpermeability, 15 which often reduces the extent of RPE abnormalities, 11 with subsequent resolution of SRF. 2 However, a global shortage of verteporfin has recently led to reduced access to PDT and a worldwide delay of treatment.…”
mentioning
confidence: 99%
“…9 Because these choroidal abnormalities presumably lie at the basis of CSC, photodynamic therapy (PDT) is a promising treatment to combat the causal changes (choroidal congestion and hyperpermeability) and their consequences (RPE abnormalities). 6,10,11 Recently, the prospective, randomized controlled PLACE and SPEC-TRA trials have shown that reduced-settings PDT achieves a significantly higher success rate for complete SRF resolution and improved functional outcomes in chronic CSC (cCSC) than other proposed therapy options, such as oral eplerenone or micropulse laser treatment. 2,[12][13][14] During PDT, the photosensitizer verteporfin is applied intravenously and then activated after 15 minutes by a 689-nm laser in a predefined area of the retina.…”
mentioning
confidence: 99%